UI/UX Design of Mobile-Based Environmental Reporting Application Using User-Centered Design Method - Sudrajat, Faozan; Lukmana Sardi, Indra; Yulia Puspitasari, Shinta (UIR PRESS, 2025)
The industrial revolution has significantly increased greenhouse gas emissions, leading to global warming and climate change, which burdens producers worldwide. In Indonesia, PT United Tractors Tbk, as a major player in the heavy equipment industry, faces challenges in the environmental reporting process due to the use of separate data collection methods between digital and non-digital (manual paper- based), which results in a lack of proper integration among aspects, making it impossible for environmental reporting to be done in real- time and causing difficulties in tracking the reporting data. This research aims to design an intuitive user interface (UI) and a seamless, satisfying user experience (UX) for a mobile-based environmental reporting application using the User-Centered Design (UCD) method, focusing on integrating all aspects of environmental reporting —including water, hazardous waste, non hazardous waste, and air—into a practical mobile platform for the company's environmental staff. The System Usability Scale (SUS) method was then employed to evaluate user satisfaction and acceptance of the developed application. The SUS results from 12 prospective users among the company's environmental staff showed an average score of 89.4, with the lowest score being 82.5 and the highest score being 100, indicating an excellent score and demonstrating that the UI/UX design is highly satisfactory and well-received by users.